Low-cost VR system for interactive education of manual assembly procedure. Issue 1 (2nd January 2023) - Grajewski, Damian; Hamrol, Adam
ABSTRACT: The article presents the concept and first results of tests of a Virtual Reality system dedicated for interactive education of manual assembly procedure. The presented solution is based on the use of a Delta robot. The main task of the robot is to simulate the shape of virtual objects as an alternative to haptic devices. The manipulator with parallel kinematics is integrated with low-cost VR equipment intended for visualization (HMD) and tracking the position of real objects (optical tracking system), and also provides manipulation of physical models (representing digital data). Experimental tests were conducted with special attention to touch interaction between the user and the end effector of the robot. An interactive VR application has been prepared for the simulation of the developed test scenarios, during which the participant of the virtual scene interacted with the simulated object. Manipulator task was to move to a location enabling such interaction. The scenario of virtual training of procedural task was also performed. The purpose of the test was to demonstrate whether the solution could be applied to work-oriented training at the production stand.